Performance improvement of novel latent thermal energy storage system with two-layer metal foam porosities - Awasthi, Abhishek; Hwang, Kwang Il; Jeon, Yongseok (Case Studies in Thermal Engineering, 2024)
A 2D numerical analysis was conducted to examine the melting performance of a shell-and-tube-type phase change material with a two-layer copper foam having higher and lower porosity levels. The design parameters for these two layers of metal foam consisted of three different volume fill ratios (VFR) (30 %/70 %, 50 %/50 %, and 70 %/30 %) and three different shapes (circular, semi-circular, and elliptical) for the lower porosity layer. The results showed that a semicircular-shaped low porosity layer with a 30 % VFR had the least melting time of 475 s. When the VFR increased to 50 %, the elliptical and circular shapes had the least melting time of 394 s. However, at a VFR of 70 %, only the elliptical shape had the least melting time of 323 s. Furthermore, the results were compared with the uniform porosity metal foam system, and deduced that the two-layer system did not always have the lower melting time compared with that of the uniform porosity system because it depended on the VFR and shape of the different porosities filled in the different layers. Additionally, for an average porosity of the metal foam, an optimal combination of two different porosities was observed for the melting performance.
Keywords: Fill ratios; Low porosity; Melting; Melting performance; Melting time; Metal foams; Shell-and-tube; Shell-and-tube-type; Tube-type; Two-layer; Melting; Metal foam; Phase change material; Shell-and-tube-type